Balanced Scorecard sebagai Instrumen Manajemen Strategis untuk Pertumbuhan UMKM di Era Digital - Purwanti Purwanti; Gopar Purnama (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the application of Balanced Scorecard (BSC) in MSMEs in the digital era. The research background highlights the importance of BSC as a comprehensive performance measurement tool amid the challenges of digitalization. The research method uses a mixed methods approach with data collection through case tracking of MSMEs that implement BSC. Data were analyzed qualitatively and quantitatively to identify constraining and supporting factors and measure the influence of BSC on MSME performance. The findings show that BSC can improve MSME performance through balancing the perspectives of finance, customers, internal processes, and learning and growth. Implementation constraints include limited resources and digital literacy, while support comes from the government and technology adoption. The implication of the research is the need for conducive ecosystem support and a BSC model tailored to the needs of MSMEs in the digital era.